Parents' involvement in children's reading :a case study in Universiti Malaysia Sarawak - Amal Hayati, Muhammad (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aimed to investigate parents’ involvement in children’s reading at home. The objectives of the study were to find out how parents are involved in their children’s reading, to examine the selection of reading materials by parents, to find out parents’ perception towards reading aloud to children and to find out parents’ perception on their involvements in children’s reading. This study involved twenty parents that were selected from a homogeneous group which were lecturers in University Malaysia Sarawak and all of them were in the same profession and in the education field. The parents were selected based on the criteria of having at least one preschool child below seven years old and they were involved in their children’s reading at home. In this study, semi structured interviews were employed as the data collection method. The first objective found out nine ways in which parents were identified involved; parents read to their children, provided their children early exposure to reading, discussed with their children what they read, monitored their children’s reading, provided guidance if their children had difficulty in reading, took their children to the library, bought books for their children, read aloud to their children and parents were a good role model for reading. The second objective found that parents were concerned with their children’s reading by providing lots of reading materials at home for their children’s reading convenience and preferred to purchase reading materials for their children. The third and fourth objectives found out that parents had positive perceptions toward reading aloud strategy and had positive perceptions on their involvements in children’s reading.